Rarely convergent sequences in topological spaces - Öner, Tarkan (Kuwait Journal of Science, 2020)
In this work, by using rare sets, we introduce a new type of convergence in topological spaces, called rare convergence, which is weaker than ordinary convergence. After presenting some examples, we investigate the relationship of rare convergence with continuity and rare continuity. Using rare convergence, we also construct a new topology, called rarely sequential topology, which is coarser than sequential topology.